Trends of Concurrent Ankle Arthroscopy at the Time of Operative Treatment of Ankle Fracture: A National Database Review. Issue 2 (April 2016) - Ackermann, Jakob; Fraser, Ethan J.; Murawski, Christopher D.; Desai, Payal; Vig, Khushdeep; Kennedy, John G.
Background. The purpose of this study was to report trends associated with concurrent ankle arthroscopy at the time of operative treatment of ankle fracture. Method. The current procedural terminology (CPT) billing codes were used to search the PearlDiver Patient Record Database and identify all patients who were treated for acute ankle fracture in the United States. The Medicare Standard Analytic Files were searchable between 2005 and 2011 and the United Healthcare Orthopedic Dataset from 2007 to 2011. Annual trends were expressed only between 2007 and 2011, as it was the common time period among both databases. Demographic factors were identified for all procedures as well as the cost aspect using the Medicare data set. Results. In total, 32 307 patients underwent open reduction internal fixation (ORIF) of an ankle fracture, of whom 313 (1.0%) had an ankle arthroscopy performed simultaneously. Of those 313 cases, 70 (22.4%) patients received microfracture treatment. Between 2005 and 2011, 85 203 patients were treated for an ankle fracture whether via ORIF or closed treatment. Of these, a total of 566 patients underwent arthroscopic treatment within 7 years. The prevalence of arthroscopy after ankle fracture decreased significantly by 45% from 2007 to 2011 ( P < .0001). When ORIF and microfracture were performed concurrently, the total average charge for both procedures drops to 4253.00 and average reimbursement to 818.00 compared with approximately 4964.00 and 1069.00, respectively, when they were performed subsequently. Conclusion. Despite good evidence in favor of arthroscopy at the time of ankle fracture treatment, it appears that only a small proportion of surgeons in the United States perform these procedures concurrently. Levels of Evidence: Therapeutic, Level IV: Retrospective